2019
DOI: 10.5213/inj.1938210.105
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Urinary Sphincter for Postradical Prostatectomy Urinary Incontinence — Is It the Best Option?

Abstract: Male stress urinary incontinence (SUI) can undoubtedly reduce quality of life and promote personal distress and psychosocial alienation. The frequency of postprostatectomy urinary incontinence (PPI) counts on the characterization of urinary incontinence and the periods of patient follow-up. Operational therapeutics, for instance, urethral male slings and artificial urinary sphincters, are well-chosen as adequate and secure surgeries for male SUI in men with continual PPI when conservative treatment is ineffect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…Current guidelines state that men with moderate SUI are candidates for either an AUS or a transobturator sling, but there are no established protocols for further stratifying these patients (6,12,13,19). In this study, we found that almost 40% of men who reported moderate SUI demonstrated severe leakage on SCT, suggesting that subjective assessment of SUI is inadequate to fully characterize SUI severity.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Current guidelines state that men with moderate SUI are candidates for either an AUS or a transobturator sling, but there are no established protocols for further stratifying these patients (6,12,13,19). In this study, we found that almost 40% of men who reported moderate SUI demonstrated severe leakage on SCT, suggesting that subjective assessment of SUI is inadequate to fully characterize SUI severity.…”
Section: Discussionmentioning
confidence: 75%
“…Prior studies have demonstrated that pre--operative 24-hour pad weight, PPD usage, and MSIGS scores are all predictors of sling success (5,(16)(17)(18)(19)(20)(21). PPD usage is a simple way to estimate SUI severity.…”
Section: Male Sui Assessmentmentioning
confidence: 99%
“…Do 5 exercises holding for 5-10 sec. Do 2 exercise sessions each day, one in the morning and one in the evening, for a total of 60 exercises prostatectomy (Ha and Yoo, 2019). Trials of PFME for post-prostatectomy urinary incontinence show that PFME reduces urinary incontinence in the first 3 months after surgery (Campbell et al, 2012).…”
Section: Pelvic Floor Muscles Exercise For Menmentioning
confidence: 99%
“…Additionally, the use of selective serotonin noradrenaline inhibitors (SSNRI), estrogens and desmopressin may be supportive. The available surgical options are manifold: paraurethral injection therapy (“bulking agents”), tension free vaginal tapes (TVTs), pubovaginal or mid-urethral urethral slings (retropubic vs. transobturatorial vs. autologous fascia), Burch colposuspension (open or laparoscopic) and artificial urinary sphincter and compression systems [ 11 , 40 , 41 , 42 , 43 ]. These interventions render a significant amelioration of the clinical symptoms and enable the recovery of continence with around 80% cure rates [ 44 ].…”
Section: Stress Urinary Incontinencementioning
confidence: 99%